농작물재해보험과 타 농가경영안정정책간의 효율적 연계방안에 관한 연구 - 최경환 (한국농촌경제연구원, 2008)
This study focused on examining the relation between crop insurance and farm management stabilization programs and maximizing synergy effects among them. The crop insurance in Korea was launched in 2001 for only two commodities, apple and pear. The number of insured commodities rose to 15 crops in 2008, and rice will be included beginning 2009. The Ministry of Food, Agriculture, Forestry and Fisheries has a plan to expand insured crops from 15 in 2008 to over 30 by 2011. The crop insurance is one of various farm management stabilization programs to compensate the economic loss incurred by agricultural production reduction caused by natural disasters and to lessen the risks to farm. The farm management stabilization programs related to crop insurance in Korea are Assistance Program for Agricultural Disaster, Flood Insurance, Direct Payments, Farm Income Stabilization Program, and Price Risk Minimization Programs. We examined the effects of the farm income protection on rice and apple farms, assuming that farms may be supported by all farm management stabilization programs. In the case of apple farms, disaster assistance payments (insurance payment+assistance program for agricultural disaster) and total assistance payments were not over 95% of lost values of apples. In the case of rice farms, however, there existed cases of assistance payments exceeding 95% of lost values, thus implying that overpayments may happen more often to crops with incomes lower than that of rice. Therefore, the government should prepare for this situation because it may cause moral hazard and budget mismanagement. Developed countries such as the USA, Japan, and Canada are using the crop insurance as a safety net for stabilizing the farm management and enlarging the revenue insurance by considering the relationship between various farm assistance payments and crop insurance. We suggested that crop insurance and other related insurances should be combined into the agriculture and fisheries insurance. Hence, the adminstration structure of the insurance should also be restructured. The government should introduce the revenue insurance and farm income stabilization programs for commodities that the insurance will have been revitalized and that have a lot of data. We studied also the linkage between crop insurance and direct payments. As for rice, we investigated the relationship between the rice income direct payment(fixed + variable) and the crop insurance. The results indicated that the combination of the fixed rice income direct payment and the revenue insurance is better than the separate implementation of the rice income direct payment(fixed + variable) and the crop insurance. With respect to orchard, the revenue insurance is better than the independent implementation of the crop insurance and the contracted shipping program. But the results are based on merely theoretical calculations. In order to execute these programs we have to examine the feasibilities because neither the data nor the circumstances for revenue insurance is not sufficient. Researchers: Kyeong-hwan Choi and Yong-lyoul Kim Research period: 2007. 12. - 2008. 6. E-mail address: kyeong@krei.re.kr and kimyl@krei.re.kr